The Mythology of the Small Community in Eight American and Canadian Short Story Cycles - Kealey, Josephene (Université d'Ottawa / University of Ottawa, 2011)
Scholarship has firmly established that the short story cycle is well-suited to representations of community. This study considers eight North American examples of the genre: four by Canadian authors Stephen Leacock, Duncan Campbell Scott, George Elliott, and Alice Munro; and four by American authors Sarah Orne Jewett, Sherwood Anderson, John Cheever, and Joyce Carol Oates. My original idea was to discover whether there were significant differences between the Canadian and American cycles, but ultimately I became far more interested in the way that all of the cycles address community formation and disintegration. The focus of each cycle is a small community, whether a small town, a village, or a suburb. In all of the examples, the authors address the small community as the focus of anxiety, concern, criticism, and praise, with special attention to the way in which, despite its manifold failings, the small community continues to inspire longings for the ideal home and source of identity. The narrative feature that ultimately provided the critical framework for the study is the recurring presence of the metropolis in all of the eight cycles. The city, set on the horizons of these small communities, consistently provides a backdrop against which author and characters seem to measure and understand their lives. Always an influence (whether for good or bad), the city’s presence is constructed as the other against which the small community’s identity is formulated and understood. The relationship between small community and city led me to an investigation into the mythology of the small community, a mythology that sets the small community in opposition to the city, portraying the former as the keeper of virtue and the latter as the disseminator of vice. The cycles themselves, as I increasingly discovered, challenge the mythology by identifying how the small community depends, in large part, on the city for self-understanding. The small community, however, as an idea, and a mythic ideal, is never dismissed as obsolete or irrelevant.
Keywords: Short Story Cycle; American Literature; Canadian Literature; Small Community; Small Town; Duncan Campbell Scott; Stephen Leacock; George Elliott; Alice Munro; Sarah Orne Jewett; Sherwood Anderson; John Cheever; Joyce Carol Oates; Twentieth Century